GEOCHRONOLOGY OF THE METAMORPHIC ROCKS IN THE KURAI ACCRETIONARY PRISM (SOUTH-EASTERN GORNY ALTAI) - A. V. Kulikova; M. M. Buslov; A. V. Travin (Геодинамика и тектонофизика)
The paper provides a review of the published and new geological and geochronological data on the metamorphic rocks in the Kurai accretionary prism, considering the evolution of the Kuznetsk-Altai island-arc paleosubduction channel of the Siberian continent. The following two stages are distinguished by 40Ar/39Ar and U/Pb dating: (1) 636–619 Ma and earlier: sinking of ophiolites into the subduction zone; (2) 604–585 Ma: sinking of the large bodies of oceanic uplifts into the subduction zone. These processes led to the exhumation of the high-pressure rocks and the hot Chagan-Uzun peridotites. The dynamo-thermal effect of the latter on the basalts is reflected in the inverted metamorphic zoning and the occurrence of garnet amphibolites and plagiogranite migmatites. It is probable that the paleo-seamounts collided with the island arc during the Vendian–Early Cambrian. The data reviewed in this paper give evidence of an active margin of the West Pacific type in the western Altai-Sayan folded region in the Vendian–Cambrian.